2016
DOI: 10.1021/acs.est.6b00505
|View full text |Cite
|
Sign up to set email alerts
|

Solar Inactivation of Enterococci and Escherichia coli in Natural Waters: Effects of Water Absorbance and Depth

Abstract: The decay of sewage-sourced Escherichia coli and enterococci was measured at multiple depths in a freshwater marsh, a brackish water lagoon, and a marine site, all located in California. The marine site had very clear water, while the waters from the marsh and lagoon contained colored dissolved organic matter that not only blocked light but also produced reactive oxygen species. First order decay rate constants of both enterococci and E. coli were between 1 and 2 d(-1) under low light conditions and as high as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 45 publications
3
67
0
Order By: Relevance
“…With respect to the latter, several studies have found bacteria sourced from wastewater to be less susceptible to sunlight than laboratory-grown organisms, 150,151,164 although another study found that differences depended on the water quality. 169 A faster growth rate during culturing was reported to increase the susceptibility of both E. coli 170 and Ent. faecalis cells to sunlight wavelengths, and stationary phase Ent.…”
Section: Effects Of Bacterial Physiologymentioning
confidence: 99%
“…With respect to the latter, several studies have found bacteria sourced from wastewater to be less susceptible to sunlight than laboratory-grown organisms, 150,151,164 although another study found that differences depended on the water quality. 169 A faster growth rate during culturing was reported to increase the susceptibility of both E. coli 170 and Ent. faecalis cells to sunlight wavelengths, and stationary phase Ent.…”
Section: Effects Of Bacterial Physiologymentioning
confidence: 99%
“…A number of studies have therefore investigated bacterial photoinactivation in the context of environmental water quality (1)(2)(3)(4)(5)(6)(7), with further studies also focusing on photoinactivation in drinking water treatment (8)(9)(10)(11), photodynamic therapy (12)(13)(14)(15), and wastewater treatment (16)(17)(18)(19)(20). Bacteria can be inactivated by sunlight by direct and indirect mechanisms.…”
mentioning
confidence: 99%
“…The majority of previous work on bacterial photoinactivation mechanisms in aquatic environments has focused on fecal indicator bacteria (FIB), such as enterococci, fecal coliforms, and Escherichia coli (2,5,6,11,19,(22)(23)(24), which are the basis of recreational and drinking water quality monitoring criteria (25) and have served as process indicators for decades. Fewer studies have investigated photoinactivation mechanisms of bacterial pathogens in aquatic environments (13,(26)(27)(28).…”
mentioning
confidence: 99%
“…Disinfection is predominantly sunlight driven by various mechanisms which are mostly dependent on the ultraviolet (UV) spectrum (Davies-Colley et al, 2000;Maïga et al, 2009a,b;Bolton et al, 2010;Fisher et al, 2011;Kadir and Nelson, 2014;Nguyen et al, 2014Nguyen et al, , 2015Silverman et al, 2015;Maraccini et al, 2016;Silverman and Nelson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This has also generated interest in developing sunlight disinfection models that resolve disinfection in a spatially dependent manner (e.g. 4 Maraccini et al, 2016) and take wavelength dependence into account (e.g. Fisher et al, 2011;Nguyen et al, 2014Nguyen et al, , 2015Silverman and Nelson, 2016).…”
Section: Introductionmentioning
confidence: 99%